OP0019 Baricitinib in systemic lupus erythematosus (SLE): results from a phase 2, randomised, double-blind, placebo-controlled study. (12th June 2018) - Wallace, D.J.; Furie, R.A.; Tanaka, Y.; Kalunian, K.C.; Mosca, M.; Petri, M.A.; Dorner, T.; Cardiel, M.H.; Bruce, I.N.; Gomez, E.; Carmack, T.; Janes, J.M.; et al.
Abstract : Background: Baricitinib (Bari), an oral selective inhibitor of Janus kinase (JAK)1 and JAK2, has been approved for the treatment of RA in the EU and Japan. Objectives: To report results from a 24 week (wk) global, Phase 2, double-blind, placebo (PBO)-controlled study of Bari in patients with SLE receiving standard therapy. Methods: Patients with SLE (positive ANA or anti-dsDNA, clinical SLEDAI-2K≥4, arthritis or rash required) receiving stable background SLE therapy were randomised 1:1:1 to PBO, or Bari (2- or 4 mg) once daily. The primary endpoint was resolution of SLEDAI-2K arthritis or rash at wk 24. Results: Of 314 patients randomised, 79%, 82%, and 83% completed 24 wks of treatment in PBO, Bari 2 mg, and Bari 4 mg groups, respectively. At wk 24, a significantly greater proportion of patients in Bari 4 mg group compared to PBO achieved resolution of SLEDAI-2K arthritis or rash (67% vs 53%, p<0.05); and SRI-4 response (64% vs 48%, p<0.05). At Wk24, the proportion of patients achieving flare reduction (SELENA-SLEDAI Flare Index [SFI]), Lupus Low Disease Activity State (LLDAS), and tender joint count (TJC) change from baseline were also significantly improved for Bari 4 mg compared to PBO (table 1). No statistically significant differences were observed between Bari 2 mg and PBO in any of the above endpoints. Rates of AEs leading to treatment discontinuation and SAEs were higher for both Bari dose groups compared to PBO. There were no deaths, malignancies, major adverse cardiovascular events, tuberculosis, or serious herpes zoster infections; one SAE of deep vein thrombosis was reported in a patient with risk factors (Bari 4 mg group). Data are n (%) patients, unless otherwise indicated. D=least squares mean change from baseline. ‡ Includes up to 30 days post treatment. CLASI=Cutaneous Lupus Erythematosus Disease Area and Severity Index; n=number of patients in the analysis population; n=number of patients in the specified category; TEAE=treatment emergent adverse event.*p≤0.05. Conclusions: In patients with SLE receiving standard background therapy, once-daily oral Bari 4 mg was associated with significant clinical improvements compared to PBO and an acceptable benefit/risk profile. These findings support further study of Bari 4 mg as a potential therapy for patients with SLE. Disclosure of Interest: D. Wallace Consultant for: Eli Lilly and Company, EMD Merck Serono, Pfizer, GSK, R. Furie Consultant for: Eli Lilly and Company, Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Takeda, Bristol-Myers, Chugai, Astellas, Abbvie, MSD, Daiichi-Sankyo, Pfizer, Kyowa- Kirin, Eisai, Ono, Speakers bureau: Daiichi-Sankyo, Astellas, Pfizer, Mitsubishi-Tanabe, Bristol-Myers, Chugai, YL Biologics, Eli Lilly, Sanofi, Janssen, UCB, K. Kalunian Consultant for: Eli Lilly and Company, M. Mosca: None declared, M. Petri Consultant for: Eli Lilly and Company, T. Dorner Grant/research support from: Roche/Chugai, Janssen, Sanofi, Consultant for: AbbVie, Celgene, Eli Lilly, Roche, UCB, MSD, Pfizer/Hospira, Novartis, Speakers bureau: Amgen, Celgene, Biogen, M. Cardiel Grant/research support from: Pfizer, Gilead, Roche, Janssen, Consultant for: Eli Lilly and Company, Pfizer, Speakers bureau: Eli Lilly and Company, Pfizer, Abbvie, I. Bruce Grant/research support from: Genzyme, GSK, Consultant for: BMS, Eli Lilly and Company, GSK, Astra Zeneca, Speakers bureau: GSK, E. Gomez Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, T. Carmack Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, J. Janes Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Linnik Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Silk Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, R. Hoffman Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company